2017
DOI: 10.1002/clc.22748
|View full text |Cite
|
Sign up to set email alerts
|

Deceleration capacity of heart rate predicts 1‐year mortality of patients undergoing transcatheter aortic valve implantation

Abstract: Background Risk prediction in patients with severe aortic stenosis (AS) undergoing transcatheter aortic valve implantation (TAVI) is challenging. Development of novel markers for patient risk assessment is of great clinical value. Deceleration capacity (DC) of heart rate is a strong risk predictor in post‐infarction patients. Hypothesis DC provides prognostic information in patients undergoing TAVI. Methods We enrolled 374 consecutive patients with severe AS undergoing TAVI. All patients received 24‐hour Holte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“… 6 DC has already been proved to be a powerful predictor of mortality in persons with myocardial infarction, heart failure, cancer, aortic stenosis, syncope, stroke and pneumonia. 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 Recently, a retrospective, observational case series emphasized direct and indirect affection of the central nervous system in COVID-19 persons with respiratory insufficiency. 14 In the current study, we postulate that impaired DC provides prognostic information in persons with COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“… 6 DC has already been proved to be a powerful predictor of mortality in persons with myocardial infarction, heart failure, cancer, aortic stenosis, syncope, stroke and pneumonia. 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 Recently, a retrospective, observational case series emphasized direct and indirect affection of the central nervous system in COVID-19 persons with respiratory insufficiency. 14 In the current study, we postulate that impaired DC provides prognostic information in persons with COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to PRD, DC was also established as a predictor of mortality in patients after myocardial infarction 6 . So far, several studies have investigated changes in DC levels under different physiologic and pathophysiologic conditions [12][13][14] . However, a clinical relevance of altered DC has only been substantiated in patients after myocardial infarction and in patients undergoing transcatheter aortic valve implantation 6,7,12 .…”
Section: Discussionmentioning
confidence: 99%
“…applied the PRSA algorithm in AC and DC of the heart rate 17 , more and more studies have found that AC and DC are related not only to physiological activity but also to a number of pathophysiological states. DC decreased gradually with age increase in normal population; 22 the magnitudes of DC and AC increased progressively as breathing frequency decreased; 28 lower DC of heart rate is a strong and independent predictor of 1-year mortality in patients with severe aortic stenosis undergoing transcatheter aortic valve implantation; 29 AC is positively associated with heart failure grade in patients with dilated cardiomyopathy; 16 lower DC assessed from short-term recordings is a strong and independent predictor of mortality and cardiovascular mortality after myocardial infarction 30 . These reports showed the complex role of ANS in the physiological and pathological process.…”
Section: Discussionmentioning
confidence: 99%